The 17th suspect [compact disc, unabridged] - Patterson, James, 1947-; Paetro, Maxine (Patterson, James, 1947- Women's murder club, 2018)
A series of shootings in San Francisco and a tip from a reluctant confidential informant lead Sergeant Lindsay Boxer to uncover disturbing activities within the police department, a situation that is further complicated by Lindsay's worsening medical problems.